2024
DOI: 10.3389/fonc.2023.1301781
|View full text |Cite
|
Sign up to set email alerts
|

Cloud platform to improve efficiency and coverage of asynchronous multidisciplinary team meetings for patients with digestive tract cancer

Yu Zhang,
Jie Li,
Min Liao
et al.

Abstract: BackgroundMultidisciplinary team (MDT) meetings are the gold standard of cancer treatment. However, the limited participation of multiple medical experts and the low frequency of MDT meetings reduce the efficiency and coverage rate of MDTs. Herein, we retrospectively report the results of an asynchronous MDT based on a cloud platform (cMDT) to improve the efficiency and coverage rate of MDT meetings for digestive tract cancer.MethodsThe participants and cMDT processes associated with digestive tract cancer wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In their study from 2023, Zhang et al presented cloud-based software for conducting a tumour board in which the participants could act asynchronously [35]. This showed that there was a high level of agreement in the opinions of the medical experts.…”
Section: Discussionmentioning
confidence: 99%
“…In their study from 2023, Zhang et al presented cloud-based software for conducting a tumour board in which the participants could act asynchronously [35]. This showed that there was a high level of agreement in the opinions of the medical experts.…”
Section: Discussionmentioning
confidence: 99%